Analisis Perbedaan Pendistribusian Laba Bersih dalam Akuntansi Konvensional dan Akuntansi Syariah pada Sektor Perbankan Tahun 2019 - Nabila Qonita; Usep Syaipudin; Ade Widiyanti (Journal on Education, 2024)
This study aims to determine differences in the distribution of profits between conventional accounting and Islamic accounting at the banks listed on the Indonesian Stock Exchange (IDX). This study uses a qualitative descriptive analysis method in which company data used are financial statements and an explanation of the desired data in this study is the 2019 financial statements.The result showed that BCA that using convensional accounting distributed their profits to stakeholders who participate in its acquistion. Meanwhile, profit distribution of BRISyariah that using Syariah Accounting also distributes their profits to stakeholders. The difference in profit distribution between conventional accounting and syariah accounting lies in how profits are shared with customers. In conventional accounting, banks distribute profits through interest, and banks using syariah accounting distribute profits through a profit-sharing system. Additionally, one key difference is in zakat distribution; only banks using Islamic accounting allocate a portion of their profits for zakat.